2020
DOI: 10.1177/1120700020959339
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictive factors of problems after fixation of trochanteric hip fractures with sliding hip screw or intramedullary devices

Abstract: Introduction: Hip fractures are common and disabling injuries, usually managed surgically. The most common type outside the joint capsule are trochanteric fractures, usually fixed with either sliding hip screw or intramedullary nail. Data are available in the National Hip Fracture Database (NHFD) on early failure and other major complications, but late or subtler complications may escape recording. This study sought to quantify such problems after fixation performed at 3different sites and identify their predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The relative risk for cut out significantly increased sevenfold for none optimal blade positioning. Despite that, multiple studies already showed an increased rate of cut out with blade position deviating from center-center and inferior-center [17][18][19][20] there were still around 88% of the patient had optimal blade positions in this study. This highlights the importance of the correct surgical technique regardless of the implant.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The relative risk for cut out significantly increased sevenfold for none optimal blade positioning. Despite that, multiple studies already showed an increased rate of cut out with blade position deviating from center-center and inferior-center [17][18][19][20] there were still around 88% of the patient had optimal blade positions in this study. This highlights the importance of the correct surgical technique regardless of the implant.…”
Section: Discussionmentioning
confidence: 55%
“…The tip apex distance was no significant predictor of implant failure in this study. In both groups mean tip apex distance was less than 25 mm, what might have prevented further cut outs compared to the results of studies including more cases with tip apex distance higher than 25 mm [ 19 , 20 ]. Tip apex distance was slightly less in FNS group.…”
Section: Discussionmentioning
confidence: 99%
“…Baumgaertner et al reported that a TAD of 25 mm or less significantly decreases the risk of screw cutout in patients with peri-trochanteric fractures that were treated with fixed-angle sliding hip screw, but this principle has been extrapolated and applied to cephalomedullary nails. 13,30,31 Subsequent biomechanical studies have suggested that when the lag screw is placed in a more inferior position, as opposed to the ideal center-center position, a TAD greater than 25mm is biomechanically stable and recent clinical studies have suggested a higher threshold TAD of 35mm. 14,32 Although TAD is the most commonly used radiographic intraoperative parameter used to assess cephalomedullary fixation, our analysis did not find a correlation between TAD greater than 25mm and fixation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding internal fixation for extracapsular intertrochanteric fractures, evidence behind the different implants used is weak considering the number of implants used worldwide. Failure of internal fixation is the most common cause of revision; in a recent retrospective study, ASA grade and the tip-apex distance are predictive of failure, while the type of implant used for internal fixation was not found to be predictive of failure [195]. Cutout rates are strongly related to the quality of reduction, more than the degree of osteoporosis, age or type of fracture [196][197][198].…”
Section: Extracapsular Hip Fracturesmentioning
confidence: 99%